Preservation of cultural heritage: a joint effort between Iran and India - Barkeshli, Mandana (New Century Publication, 2011)

(untitled)
The relations and exchanges between the great civilizations would contribute not only to the growth of the peoples of the involved civilizations but also to enrichment of lives throughout the globe. The cultural relations between Iranians and the inhabitants of the Indian Sub-continent have produced exceptional results, especially in the realm of art and culture. Looking at the history of Iran and India we can recognize the strong relations of these two cultures from Pre-Aryan civilizations and later Pre-Islamic Persia and Vedic civilization era to Muslim cultures of Mughals and Safawids. According to Pandit Jawaharlal Nehru “India and Iran are the cradle of ancient culture and civilization that continue to have their impact on the world for about 5000 years”. Protection of a culture depends, to a great extent, on the preservation of the material cultural heritage – a branch of knowledge that has received ample attention during the past couple of centuries, especially in the western world. The Eastern world, chiefly those with rich historical civilizations, too has engaged serious efforts to this task. Iran and India enjoy a common civilization background; they share interdependent cultural heritages and face similar problems in preserving them. Their joint efforts could minimize the energy input and maximize the results. It is therefore essential for the two countries – and the few other nations with whom we share a great deal of our rich history – to join hands in preserving something that may well be regarded as “world cultural heritage”. In this paper the author will present the issues of the preservation of cultural heritage in both countries and the joint efforts that has been attempted by individuals, and at the level of government bodies, to fulfill this task from 1979 to the present time. After 1979 the issues of cultural heritage in Iran entered a new phase. This new phase was because of the formation of the new university programs and establishment of the new organizations in the field. In this phase we can also notice the interest that Iran has shown towards India and its heritage. A number of people made efforts and were pioneers to fulfill these tasks. Here in this paper I try briefly to highlight some of these joint efforts, the reason behind and their impacts towards the elevation of the preservation of cultural heritage. These joint efforts will be discussed based on my involvement in certain projects, as well as my experiences - with help of other individuals to strengthen the already established ties between Iran and India in the field of education and preservation of cultural heritage. These include programs at the level of higher education, recognition of Indian academic institutions by the Iranian bodies, initiation of researches, training course, workshops, as well as a wide spectrum of quality publications in the field.